Internal consistency in a Swedish history curriculum: a study of vertical knowledge discourses in aims, content and level descriptors. Issue 1 (2nd January 2019) - Rosenlund, David
ABSTRACT: The study presented in this article examines the internal consistency of the formal Swedish history curriculum for the upper-secondary school. The research question addresses the extent to which disciplinary aspects—also referred to as vertical knowledge discourses—are transferred from fields of knowledge production to the Swedish formal history curriculum. A qualitative research design is adopted and document content analysis is used to examine the presence of vertical knowledge discourses in the aims, the core content and the level descriptors of the curriculum. The results show that a vertical knowledge discourse is present in two areas of the curriculum: the aims and the section that defines the content of history education. An exception is identified in the section of the curriculum that focuses on assessment, the knowledge requirements. Here, the presence of vertical knowledge is marginal. The conclusion is drawn that there is an inconsistency regarding the presence of vertical knowledge discourses in the Swedish history curriculum. This inconsistency can diminish the availability of vertical knowledge for the students and also lead to a situation where control over history education to some degree is transferred from curriculum designers and teachers to other agents.